Capillarity and active cell movement at mesendoderm translocation in the Xenopus gastrula - Nagel, Martina; Barua, Debanjan; Damm, Erich W.; Kashef, Jubin; Hofmann, Ralf; Ershov, Alexey; Cecilia, Angelica; Moosmann, Julian; Baumbach, Tilo; Winklbauer, Rudolf (Development, 2021)
During Xenopus gastrulation, leading edge mesendoderm (LEM) advances animally as a wedge-shaped cell mass over the vegetally moving blastocoel roof (BCR). We show that close contact across the BCR-LEM interface correlates with attenuated net advance of the LEM, which is pulled forward by tip cells while the remaining LEM frequently separates from the BCR. Nevertheless, lamellipodia persist on the detached LEM surface. They attach to adjacent LEM cells and depend on PDGF-A, cell-surface fibronectin and cadherin. We argue that active cell motility on the LEM surface prevents adverse capillary effects in the liquid LEM tissue as it moves by being pulled. It counters tissue surface-tension effects with oriented cell movement and bulges the LEM surface out to keep it close to the curved BCR without attaching to it. Proximity to the BCR is necessary, in turn, for the maintenance and orientation of lamellipodia that permit mass cell movement with minimal substratum contact. Together with a similar process in epithelial invagination, vertical telescoping, the cell movement at the LEM surface defines a novel type of cell rearrangement: vertical shearing.
Gesehen am 23.11.2021